Islamic Value-Based Recruitment Strategies for Teachers in Rumah Qur'an: A Systematic Literature Review - Nurlia, Tri Wahyu; Rindaningsih, Ida (Universitas Al-Amien Prenduan, 2024)
Recruitment of teachers in Islamic educational institutions, particularly Rumah Qur'an, plays a pivotal role in achieving effective learning grounded in Islamic values. However, challenges often arise in systematically integrating technical competencies with Islamic values. Moreover, while technology in recruitment processes promises efficiency, the moral and spiritual aspects of candidates are often difficult to assess online. This study aims to explore recruitment strategies based on Islamic values, competencies, and community involvement, as well as to identify the challenges and opportunities of digitalization in these processes. A Systematic Literature Review (SLR) approach utilizing the PICOS framework was employed to review literature from databases such as Scopus and Google Scholar, with thematic analysis conducted on trends, research gaps, and best practices. Findings indicate that Islamic values such as honesty, exemplary character, and commitment to da'wah are key elements in recruitment at Islamic educational institutions. Competency-based recruitment enhances the quality of teachers, while community-based approaches strengthen local engagement. However, digitalization faces challenges such as low digital literacy and limitations in assessing moral values online. This study contributes by offering a strategic framework that integrates Islamic values, competencies, and technology in recruitment, providing solutions to support the mission of Islamic education in the digital era.